2003
DOI: 10.1046/j.1365-3083.2003.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Enterotoxin B Upregulates Fas‐Mediated Apoptosis of Peripheral Blood Mononuclear Cells in Childhood Atopic Dermatitis

Abstract: Staphylococcal infection-producing superantigens, such as staphylococcal enterotoxin B (SEB), are presumed to play an important role of inflammatory processes in atopic dermatitis (AD). The aim of this study was to elucidate the apoptotic response of peripheral blood mononuclear cells (PBMCs) from children with AD. PBMCs from AD children were sampled and cultured with SEB stimulation. Levels of apoptosis and Fas expression were measured using flow cytometry; the soluble Fas ligand (sFasL) was also measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…First, several factors could be causing an increase in FasL concentration. Specifically, both SEB treatment of various cell types (including Jurkats) and activation of the Fas receptor [ 13 , 14 ] have been shown to cause the de novo production and secretion of soluble FasL (sFasL). Also, SEB treatment has been shown to induce the production of several members of the (tumor necrosis factor) TNF superfamily such as TNFα and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, several factors could be causing an increase in FasL concentration. Specifically, both SEB treatment of various cell types (including Jurkats) and activation of the Fas receptor [ 13 , 14 ] have been shown to cause the de novo production and secretion of soluble FasL (sFasL). Also, SEB treatment has been shown to induce the production of several members of the (tumor necrosis factor) TNF superfamily such as TNFα and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a naturally occurring mechanism by which a cell undergoes programmed death in response to external or internal signals. It has been shown that many potential biowarfare agents including Staphylococcal Enterotoxin B (SEB) improperly activate the pathways controlling this process in a variety of cell types [ 1 - 4 ]. These agents target specific components of these pathways, inducing a cascade of reactions that modify the rate at which apoptosis occurs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations